Adat Sumando: Tradisi Meminang Masyarakat Pesisir Barus, Tapanuli Tengah - Nur Sehat; Yuni Ratona Tumanggor; Thalita Fadilla (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article discusses the Sumando Traditional wedding tradition in the coastal communities of Central Tapanuli. This tradition has been carried out by coastal communities for a long time, and is still practiced today. In its history, this tradition originated from the migration of people from Poncan Island to Sibolga, and then spread to other areas around the west coast of Sumatra, including Barus, Tapanuli Tengah. This study combines two methods, namely: field research methods and literature study. Data were obtained from observations in Pananggahan Village and interviews with several traditional leaders and a number of residents. The term sumando comes from the Batak language